2016
DOI: 10.1021/acs.jpcc.5b08983
|View full text |Cite
|
Sign up to set email alerts
|

Promotion Effect of Platinum on Gold’s Reactivity: A High-Resolution Photoelectron Spectroscopy Study

Abstract: The reactivity of the Pt/Au(332) surface was studied using high resolution photoelectron spectroscopy and carbon monoxide adsorption at 3.5 x 10 -3 mbar. The characterization of Pt/Au (332) indicates the formation of a Au-Pt surface alloy at the top most atomic layer of the (332) crystal due to an atomic exchange mechanism at both terrace and step edge. The amount of alloyed Au atoms has proven to be dependent on the amount of Pt deposited in the coverage range investigated. The activation of Au atoms by alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…95,96 The same picture is further supported by the observed core level shifts shown in Figure 1F. The evolution may be assigned to surface core level shifts (SCLSs) due to strain and ligand effects that change the electron binding energy of surface atoms, 89 and to charge transfer between Au and Pt due to the difference in their workfunctions. 92 The observed Pt SCLS is large (0.7 eV) at low coverage, when Pt atoms are located in an Au-rich environment.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…95,96 The same picture is further supported by the observed core level shifts shown in Figure 1F. The evolution may be assigned to surface core level shifts (SCLSs) due to strain and ligand effects that change the electron binding energy of surface atoms, 89 and to charge transfer between Au and Pt due to the difference in their workfunctions. 92 The observed Pt SCLS is large (0.7 eV) at low coverage, when Pt atoms are located in an Au-rich environment.…”
Section: Resultssupporting
confidence: 55%
“…The above picture of the surface is consistent with prior studies of Pt deposition on Au substrates. At low coverage, Pt is known to form 2D islands on Au, with Pt embedded in the surface and subsurface layer to form a bimetallic interface. Scanning tunneling microscopy of Pt evaporated on Au(111) shows that Pt embeds in the surface layer at ϑ < 0.03 and forms alloyed islands above this coverage with the Pt concentration of the islands increasing to 50% by the point of island coalescence . Immiscibility and phase segregation in Au@Pt NCs have been observed by TEM, where, upon annealing, Pt segregates under a monolayer of Au, , consistent with theoretical predictions. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photoelectron Au 4f and Pt 4f spectra recorded at 180 eV photon energy, which allows collecting information from the top 2–3 monolayers of the alloy, are shown in Figure c,d. The high-resolution Pt 4f spectrum of pure platinum (bottom spectrum in Figure d) is represented by a single doublet with a significantly asymmetric shape at 70.95–74.25 eV, typical for metallic platinum. , In contrast, the Au 4f core level of monometallic gold (upper spectrum in Figure c) reveals the existence of two components at 83.95–87.69 and 83.6–87.36 eV, corresponding to the bulk (subsurface) and surface gold atoms. , The shape of the SRPES spectra persists for the whole range of alloy composition. Nevertheless, the continuous shift of both Pt 4f and Au 4f regions (highlighted as the 4f 7/2 peak position for Pt and Au components in Figure e) can be observed relative to the pure metals, evidencing changes in the electronic structure of both elements due to the higher electronegativity of Au. ,, Since, in our case, lower amounts of gold are dissolved in the platinum host, Pt 4f is less affected by alloying than Au 4f.…”
Section: Resultsmentioning
confidence: 97%
“…For instance, in the case of vicinal Au(332) surface modified by adsorption of Pt, the activation of Au atoms by alloying was found. The Au atoms were essential for dissociative adsorption of CO molecules on Pt/Au(332) surface at room temperature (RT) 9 , 11 . In the case of nanoalloys it was shown that the formation of Pt nanostructures on the gold based nanoparticles (NPs) improved the Pt dispersion or utilization efficiency in electrocatalysis 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%